MOOD CHOICE IN GRADUATE STUDENTS SIMULATED CONVERSATION - Destra Wibowo Kusumo; Distya Kusuma Wardani (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2020)
This study investigates the mood choice used by Indonesian English foreign language learners. The data were the spoken utterances of simulated conversation by four graduate students of English Education Department. The data were transcribed, encoded, analyzed, and interpreted based on the taxonomy of mood system, within the framework of Hallidays systemic functional linguistics, as proposed mainly by Eggins and Slade (1997) and Eggins (2004). Findings revealed that there are six types of moods, namely declarative, tagged declarative, polar interrogative, wh-interrogative, imperative, and exclamative. In addition, there are non-mood clause, namely minor clause, nonfinite clause, and incomplete clause. The dominant findings of numbers of declarative moods suggested that the exchanges of information dominate the conversation. Also, this may indicates the levels of participants competence in using casual English in foreign language context.Â